Batasan Makna Frasa Kesalahan Teknis dalam Pasal 57 Ayat (2) Peraturan Pemerintah Nomor 80 Tahun 2019 terhadap Keabsahan Kontrak Elektronik - Rahayu, Anestu Cahayoni; Dewantara, Reka; Syafi’i, R. Imam Rahmat (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the limits of the meaning of the technical error phrase in Article 57 paragraph (2) of Government Regulation Number 80 of 2019 on the validity of electronic contracts and analyze legal protection for business actors, system makers, and recipients of goods/services related to the phrase technical error in Article 57 paragraph (2) Government Regulation Number 80 of 2019. This study used a normative juridical method with a statutory and analytical approach. The results showed that the technical error phrase in Article 57 paragraph (2) of Government Regulation Number 80 of 2019 contained the meaning of default, resulting in the electronic contract being null and void. Legal protection for business actors was included in Article 6 of Law Number 8 of 1999, in the form of guarantees for self-defense when a dispute occurred due to consumers who had bad intentions. Article 12 of Law Number 19 of 2002 explicitly explained that computer programs were one of the protected copyrighted works. It was legal protection for system makers. Legal protection for recipients of goods/services was contained in Article 46 of Law Number 8 of 1999, in the form of guarantees of justice related to the quality of the product received.